Resilience of regional economic systems: from methodology to practice - Safiullin, Marat; Elshin, Leonid; Sharapov, Azat (Revista Gestão & Tecnologia, 2024)
Abstract Foreign economic turbulence, increased risks of macroeconomic instability, different resilience potential of regions and industries to crisis manifestations, etc. stipulate the need to offer appropriate concepts and models of regional strategic development with due regard to the adjusting institutional environment and mechanisms that shape the dynamics and characteristics of modern economic growth. This study develops concepts and tools for empirically assessing the resilience of regional economic systems. The Volga Federal District (Russia) constituent entities are the research object. The basis of the original concept is a 3D model that assumes the need to study resilience in the context of three key components. The first characterizes the readiness of the research object for systemic transformations. The other two components (export dependence and import dependence), combined into an aggregated indicator, form the potential for assessing the vulnerability of regions during the transformation of foreign economic relations. The result is the assessment of the resilience of regional economic systems, which lays the basis for developing solutions in regional policy in the context of systemic transformations expressed in sanctions against the Russian economy.